Pengaruh Jalur Afektif dan Jalur Rasional Terhadap Niat Beli Konsumen Dalam Social Commerce Berbasis Video Streams di Indonesia - Bagus Triaditya Putra; Muhammad Ridho Sanjaya; Fatik Rahayu (Jurnal Manajemen dan Profesional, 2026)
This study examines the effects of affective and rational routes on purchase intention in live streaming social commerce in Indonesia. The affective route (emotion and social presence) and rational route (information quantity and quality) were analyzed using SEM-AMOS. Results show that emotion and social presence enhance perceived similarity, while information quantity and quality increase perceived power. Both perceived similarity and perceived power significantly drive purchase intention, indicating that affective and rational mechanisms work simultaneously.